The complete chloroplast genome of the invasive alligator weed Alternanthera philoxeroides (Caryophyllales: Amaranthaceae). Issue 1 (2nd January 2019) - Duan, Ren-Yan; Xiang, Guo-Hong; Luo, Yu-Cai
Abstract: Alternanthera philoxeroides is an invasive amphibious herbaceous clonal plant. The chloroplast (cp) genome of A. philoxeroides is 151, 972 bp long. It encodes a set of 111 unique genes (including 78 protein coding, 29 tRNA, and four rRNA g enes). Besides, 11 genes ( atpF, ndhA, ndhB, rpoC1, rps12, rps16, trnA-TGC, trnI-GAT, trnK-TTT, trnL-TAA, and trnV-TAC ) possess a single intron, and another two genes ( clpP and ycf3 ) have double introns. A neighbour-joining (NJ) phylogenetic analysis revealed that the cp genome of A. philoxeroides is closely related to that of Amaranthus tricolor, Amaranthus hybridus, Amaranthus caudatus, and Amaranthus hypochondriacus.